THE PACIFIC VECTOR OF SPATIAL DEVELOPMENT OF RUSSIA AND THE USA IN XVII-XX CENTURIES AND TRANSFORMATION OF THEIR GEOPOLITICAL RELATIONS - Baklanov, Petr; Shvedov, Vyacheslav; Romanov, Matvey (Revista Inclusiones, 2020)
The article considers spatial aspects of the formation and transformation of the Russian-American geopolitical relations in the Northern Pacific. It is established that the spatial development of Russia and the US in the 17th - 19th centuries towards the Pacific Ocean occurred almost simultaneously. The stages of the spatial development of these countries during the specified period are allocated. The pacific policy of Russia and the US was built on mutual support for a long period of time. In many cases, it was based on the joint opposition to hegemonic ambitions of Great Britain, including military support to each other during the Crimean War (1853 - 1856) and the American Civil War (1861-1865). Gained trust in allied relations and hope on their stability promoted transfer by Russia of its American assets to the United States (Fort Ross in California and Alaska). However, from the end of the 19th century, the Russian-American geopolitical relations gradually took a turn for the worse. Later, their relations have deteriorated even more after the establishment of the Soviet political system in Russia. This phenomenon has received a pause only in the years of joint struggle against the German and Japanese aggression. Nevertheless, the relations of geopolitical rivalry between Russia (then the USSR) and the US had no mutual spatial claims. However, Mikhail Gorbachev's course to ‘new political thinking’ has allowed the US to annex the vast sector of the Bering Sea (Baker-Shevardnadze Agreement, 1990).